Ligand-controlled regiodivergent π-allyl palladium catalysis enables a switch between [3+2] and [3+3] cycloadditions. Issue 32 (2nd April 2019) - Xia, Yu; Bao, Qiao-Fei; Li, Yuke; Wang, Li-Jing; Zhang, Bo-Sheng; Liu, Hong-Chao; Liang, Yong-Min
Abstract : Reported herein is the use of ligands to tune the regioselectivity and reactivity of palladium-catalyzed [3+2] and [3+3] cycloadditions. Abstract : Reported herein is the use of ligands to tune the regioselectivity and reactivity of palladium-catalyzed [3+2] and [3+3] cycloadditions. Diverse synthesis with vinylethylene carbonates (VECs) as well as free naphthols has been explored to construct four different valuable polycyclic frameworks in a broad substrate scope.